Optimalisasi Peran Masyarakat Lokal dalam Pelayanan Prima sebagai Penggerak Ekonomi Kreatif di Kawasan Kota Tua Padang - Mariyanti, Eka; Wijaya, Riani Sukma; Abdilla, Mohammad; Fatma, Siti; Kobal, Hardinalis; Sari, Puti Embun; Marvidola, Triska; Putra, Ramadhani Kirana; Nasrah, Rasidah (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
This community service activity focuses on strengthening excellent service as a key strategy for enhancing tourism and the creative economy in the Kota Tua Padang area. The topic was selected based on the strategic role of service quality in shaping tourist satisfaction, destination image, and the sustainability of community-based tourism. The activity was implemented using a participatory approach through education, training, simulation, and mentoring of tourism actors and local communities. The results indicate positive changes in participants’ attitudes and service behavior, particularly in hospitality, responsiveness, empathy, and awareness of cleanliness and safety within the destination area. In addition, the activity increased community awareness of the potential of creative economy sectors as drivers of local economic growth. These findings confirm that excellent service is not only a determinant of tourist satisfaction but also an important instrument for strengthening community-based tourism and creative economic development.